Exploring perceptions of goodness among the Malaysian and Chinese university students: a focus group study - Ahmed Hashmi, Madiha; Waheed, Moniza; Tamam, Ezhar; Krauss, Steven Eric; Ahmad, Abdul Mua'ti @ Zamri (Nova Southeastern University, 2017)
The notion of goodness is implicitly central to the discourse relating to person perception. To date, no empirical research has focused solely upon understanding the notion of goodness and how it’s perceived and discerned in others. Utilizing focus group interviews, this paper explores how people perceive and interpret goodness in collectivist cultures of Malaysia and China. Findings revealed that Malaysian and Chinese participants had somewhat similar notions about goodness. “Concern for others’ welfare” was found to have the most resonance across the two nationalities as a key element in discerning goodness in others. Another category emerging from the findings was labelled as “Goodness a subjective notion” which encapsulated additional interpretations surrounding goodness. Directions for future research are discussed.